Evolving Malaysia - Ani, Mohd Hanafi (The Malaysian Insider, 2009)
Towards the end of the 12th century, while Western Europe was still wavering between a dying Roman influence and a dawning Gothicism, preliminaries to a medieval era which would make possible the development of a worldwide humanism, Asia had already lived through her classical period and, sinking into decay, was preparing to face a long period of political and spiritual unrest.